HUBUNGAN KOMUNIKASI INTERPERSONAL DAN IKLIM KERJA GURU DENGAN MOTIVASI KERJA GURU DI MADRASAH ALIYAH NEGERI 2 DELI SERDANG - Afwan Halim Lubis (Universitas Islam Negeri Sumatera Utara Medan, 2020)
This study aims to determine: 1) Describe the level of teacher work motivation, 2) Describe the function of interpersonal communication between fellow teachers, 3) Describe the work climate cycle of teachers, 4) Describe the relationship of interpersonal communication and teacher work climate to teacher work motivation at Madrasah Aliyah Negeri 2 Deli Serdang. In this study, the hypothesis is formulated as follows: